2004
DOI: 10.1111/j.1399-0039.2004.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐E polymorphism in patients with nasopharyngeal carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) has been known to be associated with HLA class I region. The aim of this study was to investigate the association between HLA-E and genetic susceptibility to nasopharyngeal carcinogenesis by comparing the frequencies of HLA-E alleles in 100 Thai NPC patients and 100 healthy controls. HLA-E typing was performed by means of polymerase chain reaction-sequence-specific oligonucleotide probe method. The frequency of the HLA-E*0103 allele and HLA-E*0103, 0103 genotype, but not others, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 34 publications
5
38
0
1
Order By: Relevance
“…In 1975, Simons et al first reported the association between the HLA locus and nasopharyngeal carcinoma risk (6), and a number of subsequent studies have confirmed this finding (7)(8)(9)(10). Moreover, Lu et al carried out an affected sib pair linkage analysis, and their results suggested a linkage between the HLA region and the nasopharyngeal carcinoma phenotype (11).…”
Section: Introductionmentioning
confidence: 80%
“…In 1975, Simons et al first reported the association between the HLA locus and nasopharyngeal carcinoma risk (6), and a number of subsequent studies have confirmed this finding (7)(8)(9)(10). Moreover, Lu et al carried out an affected sib pair linkage analysis, and their results suggested a linkage between the HLA region and the nasopharyngeal carcinoma phenotype (11).…”
Section: Introductionmentioning
confidence: 80%
“…The NPC susceptibility is associated with HLA-E*0103 allele, suggesting that this allele may be one of several causes contributing to NPC development. (Hirankarn et al, 2004). A genome-wide association study on NPC found significant association within the HLA region at chromosome 6p21.…”
Section: Hla-e and Hla-f In Cancer And Infectionmentioning
confidence: 99%
“…The selection of patients and control was carried out by systematic random sample. The mean age of the patients was 26.85 years (range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], and the average number of RM was 4 (range 3-6). All women selected were not having any previous live births (primary miscarriage).…”
Section: Methodsmentioning
confidence: 99%
“…The hypothesis of HLA-E allele homozygosity association with diseases was reported before in type 1 diabetes mellitus [23], nasopharyngeal carcinoma [24], HIV [25] and post-transplant complications [26,27]. Tamouza et al [26] was the first to report the association between HLA-E*0101 homozygosity and severe bacterial infections following HLA-matched unrelated donor hematopoietic stem cell transplantation and concluded that the presence of HLA-E*0101 allele could lead to inefficient presentation of bacterial peptides by the donor-derived antigen-presenting cells.…”
Section: Hla-e Genotypesmentioning
confidence: 99%
See 1 more Smart Citation